2018
DOI: 10.1891/0000-000y.32.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Risk Knowledge and Awareness of Coronary Heart Disease, and Health Promotion Behaviors Among Adults in Oman

Abstract: Interventions to increase health promotion behaviors should include application of behavioral change strategies that are suitable for age and employment status. The strategies must focus on providing information to enhance knowledge and awareness about CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…Another study also indicated a positive correlation between awareness about coronary heart disease risk factors and health-promoting behaviors (Ammouri et al 2018). Other studies have indicated that awareness of cardiovascular risk factors does not correlate with a healthy lifestyle (Johnson et al 2015;Mullie & Clarys2011).…”
Section: Discussionmentioning
confidence: 95%
“…Another study also indicated a positive correlation between awareness about coronary heart disease risk factors and health-promoting behaviors (Ammouri et al 2018). Other studies have indicated that awareness of cardiovascular risk factors does not correlate with a healthy lifestyle (Johnson et al 2015;Mullie & Clarys2011).…”
Section: Discussionmentioning
confidence: 95%
“…Without timely treatment, CHD will cause complications such as arrhythmia and angina pectoris (7). This disease, which has a long course as well as complex and severe symptoms, brings significant physical and mental discomfort to patients (8). Moreover, recurrence of CHD is common.…”
Section: Discussionmentioning
confidence: 99%
“…24 Dos pacientes que estabeleceram metas gerais de autocuidado em saúde, 60,6% (20) cumpriram, o que sugere que a intervenção corroborou para um grau de consciência em saúde suficiente para incentivar mudanças de hábitos e estilo de vida, algo que o conhecimento por si só não é capaz. 27 A meta geral mais cumprida no tocante às demais práticas de autocuidado (75,0%; 3) condiz com o fato já apontado pela literatura, de que pacientes anticoagulados procuram um estilo de vida que esteja em consonância com a capacidade de manejar a própria condição de saúde.…”
Section: Discussionunclassified
“…31 Com essa finalidade, metodologia de Freire tem a capacidade de prover o pensamento crítico e consciência sobre o problema de saúde e a importância do seu tratamento, necessários no contexto em que muitos indivíduos com fibrilação atrial não os detêm, segundo a literatura. 27,32,33 Isso ocorre a partir do momento em que se dá o entendimento da própria realidade social vivida, a qual pode se traduzir na criação de estratégias de mudança e decisão compartilhada. 23,29 Estudos demonstraram que um ambiente facilitador para o compartilhamento de experiências, dúvidas e inseguranças dos pacientes é fundamental para executar ações de educação em saúde.…”
Section: Rbfhssunclassified